Three new VHS–DES quasars at 6.7 < z < 6.9 and emission line properties at z > 6.5. Issue 2 (29th May 2019) - Reed, S L; Banerji, M; Becker, G D; Hewett, P C; Martini, P; McMahon, R G; Pons, E; Rauch, M; Abbott, T M C; Allam, S; Annis, J; Avila, S; et al.
Abstract: We report the results from a search for z > 6.5 quasars using the Dark Energy Survey (DES) Year 3 data set combined with the VISTA Hemisphere Survey (VHS) and WISE All-Sky Survey. Our photometric selection method is shown to be highly efficient in identifying clean samples of high-redshift quasars, leading to spectroscopic confirmation of three new quasars – VDES J0244−5008 ( z = 6.724), VDES J0020−3653 ( z = 6.834), and VDES J0246−5219 ( z = 6.90) – which were selected as the highest priority candidates in the survey data without any need for additional follow-up observations. We have obtained spectroscopic observations in the near-infrared for VDES J0244−5008 and VDES J0020−3653 as well as our previously identified quasar, VDES J0224−4711 at z = 6.50 from Reed et al. We use the near-infrared spectra to derive virial black hole masses from the full width at half-maximum of the Mg ii line. These black hole masses are ≃1–2 × 10 9 M⊙ . Combined with the bolometric luminosities of these quasars of L bol ≃ 1–3 × 10 47, these imply that the Eddington ratios are high, ≃0.6–1.1. We consider the C iv emission line properties of the sample and demonstrate that our high-redshift quasars do not have unusual C iv line properties when compared to carefully matched low-redshift samples. Our new DES + VHS z > 6.5 quasars now add to the growing census of luminous, rapidly accreting supermassive black holes seen well into the epoch of reionization.